Analysis Of Middle East Geopolitical Conflict Which Causes An Increase In Fuel Prices Against Indonesia's State Budget - Andhriyansyah Wirayudha Khristianto; Anisa Kusumawardani (Pasundan Social Science Development, 2026)
The escalation of geopolitical conflict in the Middle East region and fluctuations in global crude oil prices pose significant systemic challenges to Indonesia's macroeconomic stability and fiscal resilience.As a net oil importer, Indonesia is highly vulnerable to global energy price fluctuations, often triggered by disruptions to strategic distribution channels, such as the current situation in the Strait of Hormuz. This study aims to analyze the impact of Middle Eastern geopolitical conflicts on the Indonesian State Budget (APBN) that have led to rising oil prices.Through a systematic literature review, it was found that the surge in world oil prices triggered a domino effect in the form of an increase in the domestic inflation rate, a weakening of the Rupiah exchange rate, and an increase in interest rates in the short to medium term.On the fiscal side, despite additional revenue from the oil and gas sector, the burden of energy subsidy and compensation spending has increased significantly, resulting in a widening budget deficit and pressure on the primary balance. The literature used shows that every USD 1 per barrel increase in oil prices can increase the net fiscal deficit because government spending to protect people's purchasing power exceeds the windfall revenue received. As a mitigation strategy, the government needs to reallocate the budget to non-flexible strategic projects, implement more selective and targeted energy subsidies, and accelerate the transition to renewable energy to reduce dependence on imported fossil fuels in the future.